2009
DOI: 10.1590/s0100-879x2009000300007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three exercise programs on patients with chronic obstructive pulmonary disease

Abstract: We compared the effect of three different exercise programs on patients with chronic obstructive pulmonary disease including strength training at 50-80% of one-repetition maximum (1-RM) (ST; N = 11), low-intensity general training (LGT; N = 13), or combined training groups (CT; N = 11). Body composition, muscle strength, treadmill endurance test (TEnd), 6-min walk test (6MWT), Saint George's Respiratory Questionnaire (SGRQ), and baseline dyspnea (BDI) were assessed prior to and after the training programs (12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 35 publications
(55 reference statements)
7
55
1
4
Order By: Relevance
“…Both groups had significant improvement in Saint George's Respiratory Questionnaire score (see Table 4). This is in accordance with previous studies, which also found improved health-related quality of life and dyspnea after either high-intensity 2,28,32 or lowintensity exercise training [5][6][7]27 . Although the enduranceand-strength group had a greater improvement in Saint George's Respiratory Questionnaire score, this difference was not significant, compared to the improvement in the calisthenics-and-breathing group (see Table 4).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both groups had significant improvement in Saint George's Respiratory Questionnaire score (see Table 4). This is in accordance with previous studies, which also found improved health-related quality of life and dyspnea after either high-intensity 2,28,32 or lowintensity exercise training [5][6][7]27 . Although the enduranceand-strength group had a greater improvement in Saint George's Respiratory Questionnaire score, this difference was not significant, compared to the improvement in the calisthenics-and-breathing group (see Table 4).…”
Section: Discussionsupporting
confidence: 93%
“…2,4 Programs that include high-intensity exercise (such as endurance and strength training) and lowintensity training (such as callisthenic exercises in the sitting and standing position, moving the upper limbs against gravity) improve outcomes that are relevant to patients (eg, overall dyspnea, functional performance, and health status). 2,[5][6][7] On the other hand, high-intensity programs tend to result in deeper physiological improvements, being especially efficient in increasing exercise capacity and muscle force. 2 However, an important issue not yet investigated is whether different exercise training programs result in different post-program effects on the level of physical activity in daily life in this population.…”
Section: Introductionmentioning
confidence: 99%
“…It consisted of stretching of the upper and lower limbs and treadmill exercise started at 80% of the speed and inclination obtained in the exercise treadmill test. 28 The training intensity was adjusted over the weeks by using the sensation of dyspnea as a parameter, keeping it between 4 and 6 on the Borg CR 10 scale, 29 and always keeping the heart rate at 85% of maximum. Oxygen was supplemented during exercise, when the S pO 2 was below 88%.…”
Section: Physical Training Programmentioning
confidence: 99%
“…(12) No presente estudo, viuse que sujeitos graves têm maiores benefícios nos treinos de força muscular isolado ou associado ao treinamento aeróbico e que a união dos treinamentos demonstraram uma melhora na qualidade de vida quando comparado com o treinamento de aeróbico isolado ou somente o treinamento da musculatura respiratória. (8) Em relação à associação dos treinos, a revisão sugere que os achados corroboram para uma melhora da força muscular e da capacidade para realizar exercícios nos dois regimes de músculos dos membros superiores, latíssimo do dorso, peitoral maior e abdominais durante um mínimo de seis semanas de treino por 2 a 3 vezes por semana, (16) sendo necessário maiores estudos que protocolem número de repetições e séries e que avaliem diretamente a função pulmonar.…”
Section: Discussionunclassified